P060 Post-inflammatory visceral pain induced by DNBS: Preclinical features for novel therapeutics. (16th January 2018) - Lucarini, E; Di Cesare Mannelli, L; Micheli, L; Trallori, E; Antonioli, L; Fornai, M; Blandizzi, C; Ghelardini, C
Abstract: Background: The management of abdominal pain is a major problem in patients with inflammatory bowel diseases (IBDs), particularly because a significant percentage of patients continue experiencing pain also when they are in remission from a clinical and endoscopic standpoint. Current evidence suggests that it is due to the sensory pathways sensitisation during inflammation that leads to persistent changes in afferent neurons and central nervous system pain processing. Despite the high prevalence, pharmacological treatments for chronic visceral pain are still limited and ineffective, since suitable animal models to investigate the aetiopathogenesis and mechanisms of this disorder are lacking. The aims of the present study were 1) to assess the intensity and duration of visceral pain in the animal model of colitis induced by colonic instillation of dinitrobenzene sulfonic acid (DNBS); 2) to pharmacologically characterise the type of pain observed during the different stages of the disease. Methods: Colitis was induced in rats through the intra-colonic instillation of DNBS (30 mg in 0.25 ml EtOH 50%). Behavioural tests and histological evaluation of bowel epithelium were performed 7, 14, and 21 days after DNBS administration. Visceral sensitivity was assessed by measuring the magnitude of abdominal Visceral Motor Reflex (VMR) in response to CRD (Colo-Rectal Distension) in the animals under light anaesthesia, while behavioural alterations related to pain perception (abdominal withdrawal response and spontaneous motility) were assessed in awake animals. The acute effect of reference drugs on visceral sensitivity was evaluated both 7 and 14 days after colitis induction. Results: DNBS induced a significant increase in visceral sensitivity, which lasted until the 21st day after intra-colonic instillation. The measures performed after the stimulation of different gut regions generated the same results. Visceral pain threshold and spontaneous motility related to pain perception resulted lowered in awake animals 7, 14, and 21 days after colitis induction. Morphine (10 mg kg −1 s.c.) and amytriptiline (15 mg kg −1 i.p.) significantly reduced visceral hypersensitivity as well as otilonium bromide (20 mg kg −1 p.o.). Pregabalin (30 mg kg −1 i.p.) was partially effective starting from the day 14. Ibuprofen (100 mg kg −1 p.o.) and dexamethasone (0.6 mg kg −1 i.p.) did not influence visceral sensitivity at any time. Conclusions: Intra-rectal injection of 30 mg DNBS in rats induces a reproducible and long-lasting alteration of visceral sensitivity and pain-related behaviour. The similarity between the animal model and what observed in clinical strengthens the validity of its use to study novel treatments for chronic post-inflammatory visceral pain.